Achieving lipid goals in type 2 diabetic patients with dyslipidemia: barriers to treatment—the patient perspective - YAVUZ, DİLEK (My University, 2023)
Objective: Statin treatment compliance and achieving target levels differ between populations. This study aimed to determine the status of achieving the lipid targets and evaluate patients’ compliance to statin treatment in type 2 diabetic patients with dyslipidemia. Method: This cross-sectional study included type 2 diabetes mellitus (T2DM) patients with dyslipidemia who applied for treatment at our polyclinics. Statin compliance was evaluated using the Modified Morisky Adherence Scale (MMAS-8) through a face-to-face interview. Cardiovascular (CV) risk was calculated according to the 2019 ESC (European Society of Cardiology) criteria by evaluating the patients’ individual risk factors. LDL targets were determined according to risk categories with the same criteria. Results: A total of 504 patients (F/M: 274/230) were included. The serum LDL levels were 102.6 ± 39.2 mg/dL. Of the patients, 56.1% were under statin treatment. CV risk was very high in 73.6% of patients. LDL levels were significantly lower in users than in non-users (91.2 ± 26.0, 117.3 ± 38.4, p < 0.0001). The rate of reaching the LDL target was 14.8% in statin users. Treatment compliance was low for 40.6% of statin users. Discontinuation of statin treatment due to side effects was 15.7% (n = 14). N = 49 patients willingly discontinued statin treatment. They reported that 40.8% considered the treatment unnecessary. Conclusion: It was observed that 56.1% of type 2 diabetic patients were on statin therapy. A small percentage of them 14.8% (n = 42) reached the LDL target. Statin non-compliance and a lack of awareness of the statin treatment are the main reasons for high LDL levels in type 2 diabetic patients.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; ENDOCRINOLOGY & METABOLISM; MEDICINE, GENERAL & INTERNAL; Dahiliye; Endokrinoloji, Diyabet ve Metabolizma; Internal Medicine; Endocrinology, Diabetes and Metabolism; Diabetes mellitus; Hyperlipidemia; Medication adherence; Statin